Fostering the diffusion of general purpose technologies: Evidence from the licensing of the transistor patents - Markus Nagler; Monika Schnitzer; Martin Watzinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
How do licensing and technology transfer influence the spread of General Purpose Technologies? To answer this question, we analyze the diffusion of the transistor, one of the most important technologies of our time. We show that the transistor diffusion and cross-technology spillovers increased dramatically after AT&T began licensing its transistor patents along with symposia to educate follow-on inventors in 1952. Both these symposia and the licensing of the patents itself played important roles in the diffusion. A subsequent reduction in royal- ties did not lead to further increases, suggesting that licensing and technology transfer were more important than specific royalty rates.
Keywords: 330